1970
DOI: 10.5808/gi.2018.16.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Imputation of Microsatellite Markers from BovineSNP50 and BovineHD BeadChip in Hanwoo Population of Korea

Abstract: Until now microsatellite (MS) have been a popular choice of markers for parentage verification. Recently many countries have moved or are in process of moving from MS markers to single nucleotide polymorphism (SNP) markers for parentage testing. FAO-ISAG has also come up with a panel of 200 SNPs to replace the use of MS markers in parentage verification. However, in many countries most of the animals were genotyped by MS markers till now and the sudden shift to SNP markers will render the data of those animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 12 publications
0
14
2
Order By: Relevance
“…1, the accuracy of our imputation results for the three metrics analyzed (C, length r 2 , and allelic r 2 ) in the different scenarios tested (SNP windows ranged between 0.5 and 10 Mb) was higher than 0.90 (C), 0.80 (length r 2 ), and 0.75 (allelic r 2 ) for all haplotype lengths. The accuracy results presented in this study were higher than those found in a previous study performed in cattle by Sharma et al (26), which reached a concordance of 0.40 and a correlation between the real and imputed microsatellites of 0.31. In addition, we have explored not only the viability of performing microsatellite imputation but also the optimum number of SNPs necessary to perform accurate imputation of microsatellite information.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…1, the accuracy of our imputation results for the three metrics analyzed (C, length r 2 , and allelic r 2 ) in the different scenarios tested (SNP windows ranged between 0.5 and 10 Mb) was higher than 0.90 (C), 0.80 (length r 2 ), and 0.75 (allelic r 2 ) for all haplotype lengths. The accuracy results presented in this study were higher than those found in a previous study performed in cattle by Sharma et al (26), which reached a concordance of 0.40 and a correlation between the real and imputed microsatellites of 0.31. In addition, we have explored not only the viability of performing microsatellite imputation but also the optimum number of SNPs necessary to perform accurate imputation of microsatellite information.…”
Section: Discussioncontrasting
confidence: 93%
“…Therefore, the large number of samples included in this study, and as a consequence, the large number of individuals genotyped in the reference population, could in uence the high accuracy rates achieved because it is necessary to impute the odd haplotypes (28) accurately and could also reduce the concordance rates obtained in the null models. Therefore, this nding explained the higher concordance rates obtained than those in previous studies on microsatellite imputation from SNP data conducted with lower sample sizes in humans (17) [1,916 samples] and cattle (26) [1,482 samples].…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The average concordance rate of the SNPs was observed to be 76.4% (Supplementary Table S5). Accuracy of imputation is known to increase with the increase in reference population size and also by including the familial genotype data in the reference population 41 . The sample size of the reference population is not large, but the numbers of SNPs were good enough to make a conclusion that the accuracy of the present data is of good quality.…”
Section: Discussionmentioning
confidence: 99%